Analysis of factors causing work accidents among oil palm harvesters at PTPN IV Dolok Ilir - Ms, Saidana Wahyudi Putra; Aidha, Zuhrina; Arrazy, Syafran (Institute of Computer Science (IOCS), 2025)
According to the ILO every year more than 250 million people experience accidents at work. Throughout 2023, 224 thousand cases of work accidents occurred in the oil palm plantation sector Based on the Occupational Safety and Health Profile, according to data from BPJS Employment, cases of work accidents in North Sumatra in 2024 reached 9,319 work accidents. Work accidents that often occur at PT Dolok Ilir Palm Oil Plantation are impaled by palm thorns, crushed by palm fronds, cut by machetes, eyes exposed to palm waste, scratched by palm fruit thorns. The purpose of this study was to determine the factors that cause the incidence of work accidents in labor workers. This research method uses quantitative with a cross-sectional approach. Sampling using the sloving formula with cluster random sampling technique. The results of the study showed that there were factors that influenced the incidence of work accidents in oil palm harvesters were age, use of PPE, and attitudes with a Sig value. < 0,05. Attitude is the most dominant factor in the incidence of work accidents with an Exp B value = 3.892, which means that a negative attitude is 3.892 times more risky than a positive attitude. It is expected that workers can increase awareness about the importance of prioritizing safety when working.